A left-right mirror symmetric model: common origin of neutrino mass, baryon asymmetry and dark matter - Wei-Min Yang (Journal of High Energy Physics)
Abstract I suggest a left-right mirror symmetric particle model as the natural and aes- thetic extension of the SM. As the left-right mirror symmetry breaking, the tiny neutrino mass is generated by the radiative mechanism, the baryon asymmetry through the lepto- genesis arises from the characteristic decay of the TeV-scale mirror charged lepton, and a KeV-mass sterile Dirac fermion eventually becomes the CDM. The model can completely account for the common origin of the neutrino mass, the baryon asymmetry and the dark matter, moreover, profoundly uncover the internal connections among them. Finally, I discuss several feasible approaches to test the model predictions and probe the new physics by near future experiments.